Multivariate analysis in provenance studies: Cerrillos obsidians case, Peru - Bustamante A. (2007)
This work was partially supported by the Consejo Nacional de Ciencia y Tecnologia del Peru (CONCYTEC) through contract No 405-2001-CONCYTEC-OAJ.